A spatially extended model to assess the role of landscape structure on the pollination service of Apis mellifera - Joseph, Julien; Santibáñez, Fernanda; Laguna, María Fabiana; Abramson, Guillermo; Kuperman, Marcelo Néstor; Garibaldi, Lucas Alejandro (Board, 2020)
Fil: Joseph, Julien Comisión Nacional de Energía Atómica, Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas, Argentina; École Normale Supérieure de Lyon. Universite Claude Bernard Lyon I. Université de Lyon, Francia